On a systemic difference between Czech and Spanish: the Czech processual adjective - Cermak, Petr (Romanica Olomucensia, 2016)
The paper analyses Spanish equivalents of Czech processual adjectives. Based on linguistic material obtained from the InterCorp parallel corpus, the article presents a typology of these equivalents and a quantification of their uses. The data from the corpus shows a predominance of two typological equivalents, adjectives and subordinate phrases.
Keywords: Czech; Spanish; processual adjectives; InterCorp parallel corpus; comparison of languages; contrastive linguistics